CMR : Nếu x^2 - y^2 - z^2 = 0 thì ( 5x-3y+4z ) . ( 5x-3y - 4z ) = ( 3x - 5y )^2
x^2-y^2-z^2=0.CMR
(5x-3y+4z).(5x-3y-4z)=(3x-5y)^2
Cho (5x-3y+4z).(5x-3y-4z)=(3x-5y)^2
CMR: x^2=y^2+z^2
Ta có \(\left(5x-3y+4z\right)\left(5x-3y-4z\right)=\left(3x-5y\right)^2\)
\(\Leftrightarrow\left(5x-3y\right)^2-\left(4z\right)^2=\left(3x-5y\right)^2\)
\(\Leftrightarrow25x^2-30xy+9y^2-16z^2=9x^2-30xy+25y^2\)
\(\Leftrightarrow16x^2=16y^2+16z^2\Leftrightarrow x^2=y^2+z^2\)
(5x - 3y + 4z) . (5x - 3y - 4z) = (3x - 5y)2
(5x - 3y)2 - 16z2 = (3x - 5y)2
25x2 - 2.5x.3y + 9y2 - 16z2 = 9x2 - 2.3x.5y + 25y2
16x2 + 9y2 - 16z2 - 25y2 = 0
16x2 - 16y2 - 16z2 = 0
x2 - y2 - z2 = 0
x2 = y2 + z2
Cho \(x^2-y^2-z^2=0\)
CMR:(5x-3y+4z)(5x-3y-4z)=\(\left(3x-5y\right)^2\)
Ta có:
\(x^2-y^2-z^2=0\)
\(16x^2-16y^2-16z^2=0\)
\(25x^2-9x^2+9y^2-25y^2-16z^2+30xy-30xy=0\)
\(\left(5x-3y\right)^2-16z^2= \left(3x-5y\right)^2\)
\(\left(5x-3y-4z\right)\left(5x-3y+4z\right)=\left(3x-5y\right)^2\)
cho x^2-y^2-z^2=0 chứng minh rằng: (5x-3y+4z)*(5x-3y-4z)=(3x-5y)^2
cho x2-y2-z2=0.CMR
(5x-3y+4z).(5x-37-4z)=(3x-5y)2
Vì x2 - y2 - z2 = 0 => x2 - y2 = z2
Biến đổi vế trái ta có:
(5x-3y+4z)(5x-37-4z)=(3x-5y)2 - 16z2
=25x2 - 30xy + 9y2 - 16(x2 - y2)
= 25x2 - 30xy + 9y2 - 16x2 + 16y2
= 9x2 - 30xy + 25y2
= (3x-5y)2 (đpcm)
nếu x^2=y^2+z^2
chứng minh rằng
(5x-3y+4z)(5x-3y-4z)=(3x-5y)^2
Ta có
\(\left(5x-3y+4z\right)\left(5x-3y-4z\right)=\left(5x-3y\right)^2-16z^2\)
\(=25x^2-30xy+9y^2-16z^2\left(!\right)\)
Thay \(x^2=y^2+z^2\) vào ! thì
\(25x^2-30xy+9y^2-16\left(x^2-y^2\right)\)
\(=\left(3x-5y\right)^2\)
Cho \(^{x^2-y^2-z^2=0.CMR:\left(5X-3Y+4Z\right)\left(5Z-3Y-4Z\right)=\left(3X-5Y\right)^2}\)
Ta có \(x^2-y^2-z^2=0\Rightarrow z^2=x^2-y^2\)
Có \(VT=\left(5x-3y+4z\right)\left(5x-3y-4z\right)=\left(5x-3y\right)^2-\left(4z\right)^2\)\(=\left(5x-3y\right)^2-16z^2=\left(5x-3y\right)^2-16\left(x^2-y^2\right)\)
\(=25x^2-30xy+9y^2-16x^2+16y^2=9x^2-30xy+25y^2\)
\(=\left(3x\right)^2-2.3x.5y+\left(5y\right)^2=\left(3x-5y\right)^2=VP\left(đpcm\right)\)
Nếu x2=y2+z2. chứng minh rằng (5x-3y+4z)(5x-3y-4z)=(3x-5y)2
ta có
(5x - 3y + 4z)(5x - 3y - 4z) = (5x - 3y)² - 16z²
= 25x² - 30xy + 9y² - 16x² + 16y²
= 25y² - 30xy + 9x² = (5y - 3x)² = (3x - 5y)²
lần sau suy nghĩ kĩ rồi hãy post lên nhé ^^
ta có
(5x - 3y + 4z)(5x - 3y - 4z) = (5x - 3y)² - 16z²
= 25x² - 30xy + 9y² - 16x² + 16y²
= 25y² - 30xy + 9x² = (5y - 3x)² = (3x - 5y)²
chứng minh rằng : (5x-3y+4z)(5x- 3y-4z)=(3x-5y)2 nếu x2=y2+z2
Ta có:
(5x – 3y + 4z)( 5x –3y –4z) = (5x – 3y )2 –16z2= 25x2 –30xy + 9y2 –16 z2
Vì x2=y2 + z2 nên 25x2 –30xy + 9y2 –16 (x2 –y2) = (3x –5y)2